PERENCANAAN INSTALASI POMPA RETURN PUMP DENGAN KAPASITAS 130 M3/JAM UNTUK EXCHANGER HEATER AMONIA - Wardjito Wardjito (Wahana Teknik, 2012)
The use of pumps in an industry is very much its role in accordance with the functions and needs, as well as the main means of production process, as well as a means of supporting the production process. Return Pump Pump Ammonia Recycle Water Heater Exchanger absolutely necessary on a heater exchanger design Ammonia in Utility Plant X in Gresik, because the pump is an integral part of the exchanger unit heater itself, so the function of the heater can work properly is to change the temperature of the ammonia of of -33 0CÂ - -10 0C. Exchanger heater design capacity 55 tons / hour, requires a return pump with a pump capacity of 130 m3/hr. From the calculation results, obtained, Head Pump: 11.25 m, pump efficiency: 76%, 1500 rpm, impeller types: closed, the pipe diameter: 6â€œ, the pump pressure, 2.1 kg/cm2, the diameter of shaft: 35 mm, nominal motor power: 5.36 hp.Â Keywords : Return Pump, Heater, Exchangers, Ammonia